ETHICS AND DATA VERIFICATION ON PAID-CONTENT BLOG (INTERPRETIVE STUDY ON INDONESIAN BLOGGER) - Svaradiva Anurdea Devi; Pinckey Triputra (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Abstrak. Akhir-akhir ini popularitas penggunaan konten blog berbayar sebagai salah satu marketing konten digital meningkat. Para peneliti menemukan bahwa terdapat lebih dari 180 blogger Indonesia yang menawarkan layanan blogger di platform sociabuzz.com per 2019. Pengguna internet sering merujuk pada review produk di blog sebelum membeli produk. Fenomena ini disadari oleh praktisi humas yang menggunakan blog sebagai cara untuk memasarkan produk mereka. Namun, belum ada penelitian terkait penerapan etika blog kepada pembuat konten blog berbayar di Indonesia. Penelitian ini berupaya menganalisis penerapan etika blogger dalam proses pembuatan konten menggunakan empat prinsip etika blogger oleh Cenite dkk. (2009) sebagai unit analisis untuk penelitian ini. Penelitian ini menganalisis pengetahuan blogger akan etika blogger dengan mewawancarai dua pemimpin komunitas blogger di Indonesia dan mengamati cara mereka menulis blog konten berbayar dan konten tidak berbayar. Peneliti mewawancarai mereka tentang proses pembuatan konten, proses verifikasi data, dan empat prinsip etika blogger, yaitu atribusi, akuntabilitas, meminimalkan bahaya, dan pengungkapan kebenaran. Peneliti menemukan bahwa atribusi dianggap penting oleh kedua narasumber, dan proses pengungkapan kebenaran dihindari dalam membuat konten berbayar. Disimpulkan bahwa kedua informan menerapkan standar ganda antara konten berbayar dan tidak berbayar. Abstract. Lately, the popularity of using blog paid-content as one of digital content marketing has risen. Researchers found that there were more than 180 Indonesian bloggers offering blogger services on the sociabuzz.com platform per 2019. Internet users often refer to a product review on a blog before buying products. This phenomenon was realized by public relations practitioners in which using blogs as a way to market their products. However, there has been no research related to the application of blog ethics to the paid blog content creators in Indonesia. This research attempts to analyze the application of ethics as a blogger in the process of content creation using the four ethical principles of bloggers by Cenite et al. (2009) as the unit of analysis for this study. This research analyzed the awareness of bloggers about the ethics of bloggers by interviewing two leaders of the blogger community in Indonesia and observed the way they write a paid-content and non-paid-content blog. Researchers interviewed them about the process of creating content, the data verification process, and the four blogger ethical principles, namely attribution, accountability, minimizing danger, and truth-telling. Researchers found that attribution was considered important by the two speakers, and the truth-disclosure process was avoided in making paid content. It is concluded that both informants applied a double standard between paid and non-paid content.